In vivo CNS Depressant and Antinociceptive Studies of Microcos paniculata Stem Extracts on Animal Model (Bangladesh Pharmaceutical Journal, 2017)
The main objective of the study was to evaluate the possible central nervous system (CNS) depressant and antinociceptive effects of methanol (MMPS), petroleum ether (PMPS), chloroform (CMPS), dichloromethane (DMPS) and aqueous (AMPS) extracts of the Microcos paniculata (M. paniculata). The CNS-depressant effect of different extracts of M. paniculata stem on Swiss albino mice was assessed by using open field, hole cross and head deep tests at 100 and 200 mg/kg dose. Analgesic effect was evaluated by acetic acid-induced writhing and hot plate methods at 100 and 200 mg/kg dose. All the extracts had exhibited significant (Pb < 0.01, Pa < 0.001) CNS depressant and analgesic effects in a dose dependant manner. MMPS had shown highest CNSdepressant effect with 93.39% inhibition of mice movement (open field), 78.92% inhibition of hole cross and 86.90% inhibition of head deeping at 200 mg/kg dose. Besides, DMPS extracts showed maximum analgesic effect with 75.52% inhibition of abdominal writhing and 65.55% elongation of paw licking time at 200mg/kg dose. Among the five extracts, MMPS possesses potent CNS depressant effect while DMPS possesses potent analgesic effect. These findings may expose effectiveness of the extracts on anxiety and pain that may help to formulate a herbal medicine or to search a lead compound.Bangladesh Pharmaceutical Journal 20(1): 39-45, 2017